Beach-Chair Versus Lateral Decubitus Positioning for Arthroscopic Posterior Shoulder Labral Repair: A Retrospective Comparison of Clinical and Patient-Reported Outcomes. Issue 8 (July 2022) - Paul, Ryan W.; Zareef, Usman; Streicher, Sydney; Osman, Alim; Erickson, Brandon J.; Freedman, Kevin B.; Hammoud, Sommer; Bishop, Meghan E.
Background: Both beach-chair and lateral decubitus patient positioning are often utilized for shoulder arthroscopy, with each offering its unique advantages and disadvantages. The surgical position is often selected according to each surgeon's preference, with no clear superiority of one position over the other. Purpose/Hypothesis: The purpose was to compare clinical and patient-reported outcomes between patients who underwent arthroscopic posterior labral repair in the beach-chair versus the lateral decubitus position. We hypothesized that patient positioning would not affect clinical and patient-reported outcomes. Study Design: Cohort study; Level of evidence, 3. Methods: A list of all patients diagnosed with the Current Procedural Terminology codes 29806 and 29807 between 2015 and 2019 was obtained from the medical records. Patients were only included if arthroscopic posterior labral repair with or without concomitant superior labral anterior to posterior repair was confirmed. Data collected for eligible patients included the number of anchors used, perioperative and postoperative complications, redislocations, subjective instability, reoperation, and revision. Patients were also contacted to complete several patient-reported outcome surveys. Preoperative data, perioperative data, and postoperative outcomes were compared between patients who underwent surgery in the beach-chair versus lateral decubitus position. Results: Overall, 126 patients were included—69 patients underwent surgery in the lateral decubitus position and 57 in the beach-chair position—with a mean follow-up of 2.6 ± 1.7 years. There were no significant pre- or perioperative differences between groups. Rates of postoperative dislocations, subjective instability, reoperations, revisions, all complications, and return to sports rates also did not differ between groups (all, P > .05). Finally, there was no difference between groups regarding postoperative pain, function, and subjective instability scores (all, P > .05). Results of the multivariate regression analysis showed that increased age was a weak independent risk factor for subjective recurrent posterior shoulder instability (odds ratio, 1.04; P = .036). Conclusion: Surgical positioning for arthroscopic posterior shoulder labral repair did not affect postoperative clinical and patient-reported outcomes. Both beach-chair and lateral decubitus position provided good outcomes for posterior shoulder labral repair, with an overall recurrence rate of 8.7%. Increased age was a weak independent risk factor for subjective recurrent instability.